2013
DOI: 10.1136/bcr-2012-007406
|View full text |Cite
|
Sign up to set email alerts
|

Hypovitaminosis D and severe hypocalcaemia: the rebirth of an old disease

Abstract: SUMMARYVitamin D deficiency, once thought to be eradicated, is becoming a frequent occurence in children, caused mainly by dietary insufficiency. The classical manifestation is rickets, but in infants severe hypocalcaemia may present as stridor, tetany, seizures or, rarely, heart disease. Here, we describe four infants who presented with complications of severe hypocalcaemia secondary to nutritional vitamin D deficiency. (1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
(22 reference statements)
0
3
0
3
Order By: Relevance
“…In all age groups, a severe vitamin D deficiency is related to bone pain of various intensity and localization (predominantly in the lower limbs and feet) as well as increased susceptibility to bone fractures. Advanced stages of nutritional rickets and osteomalacia may be even the life-threatening conditions, characterized not only by bone deformations, but also by hypocalcemic seizures ( 29 , 30 ), tetany ( 31 , 32 ), severe bone pain and significant muscle weakness ( 33 , 34 ), hypocalcemic cardiomiopathy, even resulting in circulatory failure ( 35 – 38 ), and by disorders of psychomotor and physical development ( 39 ), including short stature ( 4 , 40 ).…”
Section: Evidence Base For Updated Polish Recommendationsmentioning
confidence: 99%
“…In all age groups, a severe vitamin D deficiency is related to bone pain of various intensity and localization (predominantly in the lower limbs and feet) as well as increased susceptibility to bone fractures. Advanced stages of nutritional rickets and osteomalacia may be even the life-threatening conditions, characterized not only by bone deformations, but also by hypocalcemic seizures ( 29 , 30 ), tetany ( 31 , 32 ), severe bone pain and significant muscle weakness ( 33 , 34 ), hypocalcemic cardiomiopathy, even resulting in circulatory failure ( 35 – 38 ), and by disorders of psychomotor and physical development ( 39 ), including short stature ( 4 , 40 ).…”
Section: Evidence Base For Updated Polish Recommendationsmentioning
confidence: 99%
“…Yilmaz et al measured vitamin D, calcium, and PTH levels in 750 infants and found significantly lower vitamin D levels in preterm infants with hypocalcemia, but no significant difference in vitamin D levels between hypocalcemia and normocalcemia in term infants [ 5 ]. Nevertheless, there are multiple reports of hypocalcemic seizures in infancy attributed to VDD [ 6 , 7 ]. A population-based study in the United Kingdom estimated the incidence of hypocalcemic seizures due to VDD to be 3.49 per million children 0–15 years of age (95% CI: 2.81–4.26) and 44.36 per million in children 0-1 year of age (95% CI: 35.12–55.28) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…This condition could be secondary to nutritional deficiency and could explain the hypocalcaemic seizures this child presented in the first year of life, and the delayed achievement of motor milestones due to decreased muscle tone and recurrent infection 7 8. Despite having several risk factors for nutritional vitamin D deficiency (late preterm, dark skin, low sun exposure due to multiple hospital admissions6), normal–high serum 1.25(OH) 2 D 3 suggests a genetic aetiology: vitamin D-dependent rickets type I or II, both autosomal recessive disorders.…”
Section: Discussionmentioning
confidence: 99%